Neurophysiological Assessment of Prolonged Recovery From Neuromuscular Blockade in the Neonatal Intensive Care Unit - Soffer, Omri David; Kim, Angela; Underwood, Ellen; Hansen, Anne; Cornelissen, Laura; Berde, Charles (Frontiers in Pediatrics, 2020)
Objective: To evaluate recovery from neuromuscular blockade in infants using Train-of-Four nerve stimulation. Study Design: Ulnar nerve stimulation was used to evoke thumb twitch and reported as a Train-of-Four ratio. Thumb twitch was also recorded visually in real-time. The primary outcome was time to near recovery of muscle function (Train-of-Four ratio >70%). Secondary analyses were time to greater degrees of recovery, (Train-of-Four ratio >80%, 90%), the sensitivity of accelerometry versus visual thumb-twitch and clinical variates to assess safety. Results: Patients were enrolled following rocuronium-boluses (n=10) and vecuronium-infusions (n=9). Median recovery time to Train-of-Four ratio >70% was 14 hours following rocuronium-bolus dosing and 34 hours following cessation of continuous vecuronium infusion. The median stimulus threshold for accelerometry was 27.5 mA and visual observation was 20 mA. There were no safety concerns. Conclusion(s): Neuromuscular monitoring using Train-of-Four nerve stimulation is feasible in infants. Some infants exhibited prolonged recovery from neuromuscular-blockade. These pilot data may facilitate future standardized pediatric protocols on neuromuscular monitoring for safer dosing.